Energy Minimization Methods in Computer Vision and Pattern Recognition 9th International Conference, EMMCVPR 2013, Lund, Sweden, August 19-21, 2013. Proceedings - Heyden, Anders.; Kahl, Fredrik.; Olsson, Carl.; Oskarsson, Magnus.; Tai, Xue-Cheng. (Lecture Notes in Computer Science, 2013)
This volume constitutes the refereed proceedings of the 9th International Conference on Energy Minimization Methods in Computer Vision and Pattern Recognition, EMMCVPR 2013, held in Lund, Sweden, in August 2013. The 26 revised full papers were carefully reviewed and selected from 40 submissions. The papers are organized in topical sections on Medical Imaging; Image Editing; 3D Reconstruction; Shape Matching; Scene Understanding; Segmentation; Superpixels; Statistical Methods and Learning.